2020
DOI: 10.1186/s13756-020-00781-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of hospital disinfectants against nosocomial infection pathogens

Abstract: Background: Due to the increasing rate of hospital-acquired infections, it is essential to select appropriate disinfectant agents. In this study, the efficacy of hospital disinfectants against nosocomial infection pathogens was compared. Methods: High level disinfectants (Steranios 2%, Deconex HLDPA, and Microzed Quatenol) were tested for their antibacterial effects by determining their minimum inhibitory (MIC) and minimum bactericidal concentrations (MBC) against Enterococcus faecalis ATCC 29212 and Burkholde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Nutrient broth without disinfectant was inoculated with the bacteria and used as the positive control, while nutrient broth inoculated with the same volume of deionized water was used as the negative control. All the tubes were incubated at 35 °C for 48 h before the results were obtained [ 32 , 33 , 34 , 35 , 36 ]. The MICs of the disinfectants against CRKP strains demonstrated the highest dilution for aseptic growth.…”
Section: Methodsmentioning
confidence: 99%
“…Nutrient broth without disinfectant was inoculated with the bacteria and used as the positive control, while nutrient broth inoculated with the same volume of deionized water was used as the negative control. All the tubes were incubated at 35 °C for 48 h before the results were obtained [ 32 , 33 , 34 , 35 , 36 ]. The MICs of the disinfectants against CRKP strains demonstrated the highest dilution for aseptic growth.…”
Section: Methodsmentioning
confidence: 99%
“…The well-diffusion method was used to test the ability of the biosynthesized CNPs to inhibit the growth of multidrug-resistant Acinetobacter baumannii bacteria using swab inoculation assay method. Bacterial suspension was prepared according to the method of Amini Tapouk et al 37 . In sterilized Petri dishes, 50 mL of nutrient agar medium was poured and allowed to solidify.…”
Section: Characterization Of Chitosan Nanoparticlesmentioning
confidence: 99%
“…Furthermore, it will reduce the likelihood of bacteria developing resistance to disinfectants in the healthcare setting. The use of disinfectants merely based on the manufacturer's claims is causing increased incidents of microbes getting resistant to disinfectants (Amini et al, 2020). Hence, the results of the present study indicated that it is very important to access the antimicrobial activity of the intended disinfectant before use and that too with standardized methods.…”
Section: Discussionmentioning
confidence: 73%